Pendidikan Kesehatan Yang Service Excellent Tentang Pain Relief Pada Saat Persalinan Di Desa Bangun Rejo Kecamatan Morawa Deli Serdang Tahun 2023 - Yessica Geovany Sianipar; Ariska Fauzianty; Khairunnisa Situmorang; Nova Isabella Napitupulu; Hesti Desmawati Gulo; Erliani Br Ginting; Esra Maria Tambunan (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
Labor pain is a physiological response that occurs due to an increase in catecholamines that interfere with uterine contractions. Labor pain can be overcome with various alternatives. However, the lack of health promotion related to pain relief strategies causes the majority of pregnant women to lack information literacy on how to deal with pain relief during childbirth. This community service activity was carried out in conjunction with the KKN midwifery undergraduate students at STIKes Mitra Husada Medan in Desa Bangun Rejo, Tanjung Morawa District. The main activity program is to provide education to pregnant women who will give birth with counseling about pain relief strategies during childbirth. This community service method adopts action research steps. Evaluating the program using a questionnaire. The results of the community service which was attended by 10 third trimester pregnant women, it turned out that this activity received a good and positive response from pregnant women. Furthermore, the results of the evaluation of this counseling were obtained, 60% of pregnant women could understand and explain the definition of pain relief strategies and the goals of pain relief strategies, 70% of pregnant women could understand and explain the handling of pain relief strategies. It is hoped that village midwives can also provide health education to birth attendants about pain relief strategies that can be implemented.